2016
DOI: 10.1021/acs.jproteome.6b00090
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Characterization of an Obese Phenotype in the Zucker Rat Model Defining Metabolic Axes of Energy Metabolism and Host–Microbial Interactions

Abstract: ABSTRACT:The Zucker (fa/fa) rat is a valuable and extensively utilized model for obesity research. However, the metabolic networks underlying the systemic response in the obese Zucker rats remain to be elucidated. This information is important to further our understanding of the circulation of the microbial or host-microbial metabolites and their impact on host metabolism.1 H Nuclear Magnetic Resonance spectroscopy-based metabolic profiling was used to probe global metabolic differences in portal vein and peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 36 publications
8
12
0
Order By: Relevance
“…Ahmad et al [29] reported decreased excretion of indoxyl sulfate in obese subjects. An inverse relationship of indoxyl sulfate with BMI has also been shown in other animal and human studies [61,62].…”
Section: Other Amino Acids and Related Metabolitessupporting
confidence: 64%
“…Ahmad et al [29] reported decreased excretion of indoxyl sulfate in obese subjects. An inverse relationship of indoxyl sulfate with BMI has also been shown in other animal and human studies [61,62].…”
Section: Other Amino Acids and Related Metabolitessupporting
confidence: 64%
“…A study using a rat model investigated metabolic profiles of portal vein and peripheral blood plasma, urine, and fecal water of obese and lean animals with a major focus on circulating host-microbial metabolites. 135 This study demonstrated the important association of urinary host-microbial co-metabolites with phenotype. In another study, blood samples collected before and, periodically, after bariatric procedures were investigated to evaluate the metabolic alterations due to bariatric surgery in obese individuals.…”
Section: Applicationsmentioning
confidence: 61%
“…Therefore, it has emerged as a powerful tool to explore metabolic processes, identify crucial metabolic biomarkers and reveal metabolic mechanisms [ 3 ]. Indeed, metabolomics is particularly useful in the study of environment-gene and -protein interactions [ 4–6 ], and the discovery of novel drugs [ 7 , 8 ]. More importantly, the unique features of metabolites, as compared to proteins and nucleic acids, lead to a novel approach to use metabolites to revert biological phenotypes like antibiotic resistance, which is termed as reprogramming metabolomics [ 3 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%